SIGNIFICANCE AND ROLE OF SMALL AND MIDDLE ENTREPRISES IN ECONOMIC DEVELOPMENT - Bandur, Miodrag (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2016)
Small and middle enterprises (SME) are becoming more and more the subject of interest in developed countries in which small and middle companies represent a factor of development. The developed countries of the word put SME into focus of their economic strategies and programs and- by concrete macro-economic measures- the aimed politics to SME has a direct impact to reduction on business costs and improvement of liquidation (thus, competitive position of SME), through tax bonds. However, BiH still does not develop tax politics and praxis of many developed countries, which causes a lack of attention and improvement of the sector of SME. This is what many research in BiH confirmed. The changes in social- economic system based on the market commerce create suitable conditions for development of various activities which should be profitable and keep up with the development, with continuous adaptation to constant changes on market, which gives the advantage to SME or, so called, small business. Such companies most often represent the collision of ownership, management and risk, so the knowledge and skill needed for successful management include a very wide range.